Regol megal megol : fenomena kosmogoni Jawa - Linus Suryadi Ag. (Linus Suryadi Agustinus), 1951-1999. (Yogyakarta : Andi Offset, 1993)
Javanese culture; collection of articles.
Koleksi Sumbangan : Prof. Datuk Dr. Mohamad Hatta Shaharom (Anak Shaharom Husain)
Includes bibliographical references (p. 227-228).
Keywords: Java (Indonesia) -- Civilization